The Criminalization of Marginalized Women - Pavićević, Olivera (Zbornik Instituta za kriminološka i sociološka istraživanja, 2020)
The criminalization of women's poverty is analyzed in this paper from the perspective of the process of feminization of poverty and multiple discrimination within and outside normative femininity. The marginalization of poor women paves the way for their criminalization, which in the new neoliberal penology manifests itself as a perception of the increased risk of crime attributed to poor, uneducated, non-white and socially excluded women. The intersection of class, gender and criminal inequality opens up questions of social justice and the possibilities of achieving it when it comes to marginalized women. A critical analysis of social practices conducive to the criminalization of marginalized women should proceed from the deconstruction of neoliberal discourses and the social decontextualization to which they aspire. In that sense, open and hidden practices of discrimination, deprofessionalization, dehumanization, stigmatization, exclusion and finally criminalization of marginalized women should be revealed in the facts of the gloomy reality in which these women live, before, during and after entering or sanctioning crime.